Working-class network society communication technology and the information have-less in urban China - Qiu, Jack Linchuan, 1973- (MIT Press, 2009)
This is an examination of how the availability of low-end information and communication technology has provided a basis for the emergence of a working-class network society in China.
Keywords: Information technology -- China.; Telecommunication -- China.; Diffusion of innovations -- China.; China.; elektronické knihy; electronic books